Gender discrimination and other factors affecting Full Immunization Coverage (FIC) in 59 low performing blocks of Bihar - Singh, C M; Mishra, Abhishek; Agarwal, Neeraj; Ayub, Arshad; Mishra , Shradha; Lohani , Pallavi (Indian Journal of Community Health, 2020)
Background: Routine childhood immunization has proven to be among the most practical and most cost-effective health interventions. The full immunization coverage (FIC) has increased, still it is less. Especially in the low performing blocks of Bihar ,it is less than 70 %.There are various factors responsible for less FIC including gender discrimination also which is still hidden in the society. Hence this study was done to find out the FIC in Bihar with associated factors including gender discrimination. Objectives: To find out the various associated factors affecting FIC and to find out gender discrimination (if any) in FIC in different districts of Bihar. Methodology: Two stage cluster sampling with Probability Proportional to size Sampling (PPS) was used as per Study protocol. The study was conducted in 59 low- performing blocks of Bihar where the full immunization coverage was less than 70%. The survey was conducted in 59 blocks. From each block, 30 clusters (Villages) were selected. As a convention, 7 children of age group 12- 23 months were selected from each cluster. Thus, data collection was done for a total of 12,390 children.A structured questionnaire was formulated on the basis of WHO coverage evaluation format. Web based Application SDRC kit was used for data collection while SPSS v. 20 was used for analysis. Results: FIC was found to be 60.81% , it was higher for the rural clusters, general caste, Hindus when compared to urban clusters , SC and other castes, and Muslim religion respectively. For 1st child FIC was highest (66.8%) and was lesser for females. A coverage ratio (female to male) was found to be less than 1 for most of the districts. Conclusion: There are considerable inequities in full immunization by various individual (birth order, gender, birth weight), social (religion, caste), and societal (health care facility and cluster type) characteristics. In general, the ratio (female/male) remains less than 1 for most of the districts.